2012
DOI: 10.1039/c2ib20154b
|View full text |Cite
|
Sign up to set email alerts
|

Established and novel methods of interrogating two-dimensional cell migration

Abstract: The regulation of cell motility is central to living systems. Consequently, cell migration assays are some of the most frequently used in vitro assays. This article provides a comprehensive, detailed review of in vitro cell migration assays both currently in use and possible with existing technology. Emphasis is given to two-dimensional migration assays using densely organized cells such as the scratch assay. Assays are compared and categorized in an outline format according to their primary biological readout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 52 publications
0
63
0
Order By: Relevance
“…We hypothesize that p-ERK2 could destabilize the CDH1-catenin complex through multiple pos-Magnetically attachable stencil invasion assay. The assay was performed as previously described (39). Briefly, a magnetically attachable stencil was placed onto 12-well dishes, previously coated with monomeric collagen (0.1 mg/ml collagen I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that p-ERK2 could destabilize the CDH1-catenin complex through multiple pos-Magnetically attachable stencil invasion assay. The assay was performed as previously described (39). Briefly, a magnetically attachable stencil was placed onto 12-well dishes, previously coated with monomeric collagen (0.1 mg/ml collagen I).…”
Section: Discussionmentioning
confidence: 99%
“…Armed with the insights gained from studying Plac8.1 in zebrafish, we examined the functional consequences of overexpressing PLAC8 in HCA-7 cells (HCA-7P8). We compared the 2-dimensional (2D) invasive behavior of parental and HCA-7P8 cells using a magnetically attachable stencil invasion assay (39). Cells were seeded at high density on monomeric collagen, and cell migration was analyzed upon removal of a magnetic stencil.…”
Section: Figurementioning
confidence: 99%
“…Interested readers are directed towards a detailed review that discusses their relative merits and applications of the more novel gap-creation methods. 34 Whatever the method used, it is important to note that recent research suggests that gap geometry affects the closure rate regardless of gap surface area uniformity. 35,36 To simulate wounding, the most common approach is to create a gap by scratching a confluent monolayer with a pipette tip, needle, or other sharp tool.…”
Section: Sample Preparation: Creating the Gapmentioning
confidence: 99%
“…In vitro scratch assays are routinely used to study collective cell spreading in cancers, drug design, and tissue repair [2,7,58,65,76,77]. However, it is reported that results from scratch assays are difficult to reproduce [35,120].…”
Section: Research Questionsmentioning
confidence: 99%
“…Two-dimensional in vitro cell biology assays are routinely used to study cancer spreading, drug design and tissue repair [2,7,58,65,76,77]. These assays provide insight into collective cell spreading, as a result of combined cell migration and cell proliferation.…”
Section: Overviewmentioning
confidence: 99%